PENGARUH LOAN TO DEPOSIT RATIO (LDR), NON PERFOMING LOAN (NPL), TOTAL ASSET TURNOVER (TATO), DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2022 - Duma Rahel Situmorang; Arthur Simanjuntak; Fanny Kristina Siregar (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2023)
This study aims to examine and analyze the effect of loan to deposit ratio (LDR), non-performing loans (NPL), total asset turnover (TATO) and capital adequacy ratio (CAR) on return on assets (ROA) in banking companies listed on the stock exchange. Indonesian Securities Period 2017-2022. This type of research is a causal quantitative research and sampling technique through purposive sampling method and research data obtained 48 banks as a population and as many as 13 banks listed on the Indonesia Stock Exchange (IDX) as a sample. The data used is secondary data. The results with the t test concluded that Loan to Deposit Ratio (LDR) partially has a significant positive effect on Return on Assets (ROA), Non Performing Loans (NPL) has a significant negative effect on Return on Assets (ROA), Total Asset Turnover (TATO) has a positive effect not significant to Return on Assets (ROA), Capital Adequacy Ratio (CAR) has a positive and significant effect on Return on Assets (ROA). The results with the F test simultaneously Loan To Deposit Ratio (LDR), Non Performing Loans (NPL), Total Asset Turnover (TATO), and Capital Adequacy Ratio (CAR) have a positive and significant effect on Return On Assets (ROA).